Community college and beyond : understanding the transfer pipeline for Latina/o/x students - Del Real Viramontes, José R.; Vasquez, Marissa C. (Hispanics in education and administration., 2023)
Awarded the American Association of Hispanics in Higher Education (AAHHE) Edited Volume Book of the Year 2025 As the transfer disparity persists among Latina/o/x community college students and continues to widen for those seeking to complete their baccalaureate degree, we asked ourselves three questions: (1) How do Latina/o/x community college students navigate the transfer preparation and decision-making process? (2) Once at the university, how do Latina/o/x transfer students negotiate their identities and lived experiences as they persist towards graduation and beyond? (3) What policies, practices, and programs at both two-and four-year institutions facilitate access, persistence, and completion for Latina/o/x community college/transfer students? These reflections prompted us to seek answers. This is the first edited book to provide much needed theoretical and empirical insights on Latina/o/x students who enter postsecondary education through the community college. Our book offers a comprehensive outlook on the pre- and post-transfer experiences of Latina/o/x students written by scholars and scholar practitioners working in the field of higher education. In addition, we include specific sections that speak directly to policies, practices, and theory that address transfer pathways for Latina/o/x community college and transfer students.